Pendekatan Design Thinking pada Pengembangan UMKM di Desa Nelayan Jawa Timur - Wijayanti, Anita; Novianti, Nurlita (Jurnal ABM Mengabdi, 2024)
Limited access to infrastructure in coastal areas causes MSMEs to be exposed to economic and social problems. The Community Service Program (PKM) is an effort to reach the community, which has been largely unnoticed, especially by universities and academics. Through a Design Thinking approach, this PKM aims to understand, map, and provide solutions to the problems and potential of MSMEs in the Kondang Merak Beach Fishing Village, East Java. This approach emphasizes an iterative process through five stages: empathizing, defining, forming ideas, creating prototypes, and testing. The empathy stage succeeded in identifying various MSME problems from limited accounting, financial, and infrastructure literacy in the Fisherman Village. Socialization and assistance activities for simple bookkeeping and calculating production costs involved lecturers, students, and community empowerment activists. Indicators of the success of this program include mapping problems and potential, increasing accounting and financial literacy, developing a new Lean Canvas product, and ongoing assistance that aligns with the iterative principles of the Design Thinking approach